Varicosporellopsis shangrilaensis sp. nov. (Nectriaceae, Hypocreales), a new terricolous species isolated from the rhizosphere soil of Astragalus polycladus in northwestern Yunnan, China - Dou, Zheng-Rong; Zhang, Fa; Zhou, Guo-Jun; Gong, Gao-Fen; Ding, Jia-Jie; Fan, Xu-Hang; Jiang, Bei; Wang, Kai-Ling (Phytotaxa, 2023)
Two fungal strains were isolated from the rhizosphere soil of a Chinese medicinal herb plant, Astragalus polycladus, in northwestern Yunnan, China. Both of them were identified as a new fungal species of Varicosporellopsis based on the evidence of morphology and phylogenetic analysis of ITS, LSU, TUB and ACT sequences data. Phylogenetic analysis of combined ITS and LSU sequence data revealed that strains MTF 7 and KLF 01 belong to the genus Varicosporellopsis with the highest sequence similarity (95.51%) to the type strain V. americana CBS 148257 and formed a sister lineage to V. americana CPC 40768 with high support values (100% ML, 1.00 BI). Morphologically, V. shangrilaensis is characterized by macronematous, branched conidiophores, phialidic conidiogenous cells, reniform macroconidia and spherical microconidia. This new species is the first reported of Varicosporellopsis in China. The morphological description, illustrations and phylogenetic analysis of V. shangrilaensis are provided in this study.